APLIKASI PUPUK ORGANIK CAIR DARI CANGKANG TELUR DAN AMPAS TAHU UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL SELADA MERAH PADA SISTEM HIDROPONIK RAKIT APUNG : - Yustika Yustika; Nugraheni Widyawati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[APPLICATION OF LIQUID ORGANIC FERTILIZER FROM EGGSHELL AND TOFU DREGS ON PROMOTING GROWTH AND YIELD OF LETTUCE UNDER FLOATING RAFT HYDROPONIC SYSTEM]. Eggshell waste and tofu pulp contain nutrients that have the potential as plant fertilizers. The use of liquid organic fertilizer (LOF) from eggshells, and tofu dregs can be a source of nutrition in hydroponic cultivation at a relatively low price. The optimal growth of red lettuce plants requires a proper concentration of nutrients. This study aimed to examine the effect of the concentration of LOF from eggshells and tofu dregs that are most effective in increasing the growth and yield of red lettuce in floating raft cultivation systems. This research was conducted from December 2020 to February 2021 at the Kartini Experimental Garden, Faculty of Agriculture and Business, Satya Wacana Christian University. This study used a Randomized Complete Block Design with liquid organic fertilizer made from egg shells and tofu dregs  with different concentrations and AB mix as a comparison. The treatment consists of five levels, namely AB mix, LOF 10 mL/L, LOF 20 mL/L, LOF 30 mL/L, and LOF 40 mL/L. Observation parameters include plant height, number of leaves, leaf area, root length, and fresh and dry weight of the plant. The results of the observations were analyzed using the analysis of variance (F test 5%). On average, the HSD Tukey test followed the treatment with a confidence interval of 5%. This study showed an influence on the treatment of eggshell LOF concentration and tofu dregs  20 mL/L resulting in the highest red lettuce with 9.15 leaves, root length 38.75 cm, header fresh weight 36.33 g and highest root fresh weight 16.22 g at LOF treatment 10 mL/L. These results have not matched the application of ABmix fertilizer, which reached the fresh weight of 74.79 g.